DEROGATIONS OF ARTICLE 8 OF THE EUROPEAN CONVENTION FOR THE PROTECTION OF HUMAN RIGHTS AND FUNDAMENTAL FREEDOMS DURING A STATE OF EMERGENCY - Tubić, Bojan; Toroman, Aleksandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The right to privacy is one of the fundamental human rights, as it encompasses a wide range of relationships related to the private life of the individual. Starting with the right to family life and the right to private life, many institutions that seem very important nowadays, such as data protection, find their place and are part of the right to privacy. Nevertheless, the right to privacy is one of the relative rights protected by the European Convention, which means that it can be derogated in specific cases and under certain conditions. One of the examples of the possibility of its restriction is the epidemic of the Covid-19 virus. Considering that numerous countries around the world have restricted the right to privacy, the question is whether and to what extent the restriction was necessary, whether it was in accordance with the law and whether it served a legitimate purpose. The answers to these questions can be found by analysing the individual case in question and the past practice of the European Court of Human Rights, which are the starting factors. The purpose of this article is to examine the conditions set out in the European Convention for the derogation of right to privacy and to analyse the practice of the European Court of Human Rights.
Keywords: Article 8 of the ECHR, Covid-19, derogation, state of emergency